Reviews - Anton, Corey (Explorations in Media Ecology, 2006)
Abstract Kaha Waite, C. Mediation and the Communication Matrix. New York: Peter Lang Publishers, 2003. 193 pp. Paper $24.95, ISBN 0-820-46177-6.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9lbWUuNS40LjMyOV81